2017
DOI: 10.1242/bio.022624
|View full text |Cite
|
Sign up to set email alerts
|

The coordinating role of IQGAP1 in the regulation of local, endosome-specific actin networks

Abstract: IQGAP1 is a large, multi-domain scaffold that helps orchestrate cell signaling and cytoskeletal mechanics by controlling interactions among a spectrum of receptors, signaling intermediates, and cytoskeletal proteins. While this coordination is known to impact cell morphology, motility, cell adhesion, and vesicular traffic, among other functions, the spatiotemporal properties and regulatory mechanisms of IQGAP1 have not been fully resolved. Herein, we describe a series of super-resolution and live-cell imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…1C, right bottom),. It is possible that these cytosolic interactions occur in endosomes and/or lysosomes as IQGAP1 is known to localize to endosomes [21]. A similar interaction between IQGAP1 and PIPKIγ is also seen in NIH 3T3 fibroblasts and a liver cancer cell line HepG2 (Fig.…”
Section: Iqgap1 Associates With Pipkiγmentioning
confidence: 70%
“…1C, right bottom),. It is possible that these cytosolic interactions occur in endosomes and/or lysosomes as IQGAP1 is known to localize to endosomes [21]. A similar interaction between IQGAP1 and PIPKIγ is also seen in NIH 3T3 fibroblasts and a liver cancer cell line HepG2 (Fig.…”
Section: Iqgap1 Associates With Pipkiγmentioning
confidence: 70%
“…To do so, we employed IQGAP1-positive sorting endosomes as an experimental model as the micron size, basal confinement, low mobility, and relatively short lifetime ($1 h) of these compartments make them highly amenable to temporal imaging analyses. Again, we have previously shown that IQGAP1 intensities correlate negatively with actin at high frequencies because of the temporal relationship between transient scaffold disassociation and growth of the actin networks that surround and confine endosomes to the basal cortex of polarized epithelial MCF10A cells (26). To further characterize this apparent negative actin regulation and to probe potential coupling to other membrane development and signaling processes, we first performed a series of live cell imaging experiments to identify and characterize the temporal hierarchy of actin regulatory proteins and PI lipid species that function within the compartments.…”
Section: Resultsmentioning
confidence: 85%
“…Live cell imaging analyses indicate that the mechanism underlying IQGAP1 localization to these compartments is multifaceted and involves combinations of positive (supportive) and negative (inhibitory) interactions with actin and other protein or membrane components of the endosomal compartment. Moreover, dynamic correlation analyses indicate these interactions occur at different timescales, yielding nonmonotonic, frequency-dependent localization behaviors and scaffold/actin intensity correlations (26). For example, IQGAP1 and actin intensities tend to rise and fall together over long timescales (>10 min) as compartments assembled and disassembled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average the duration of IQGAP1-mediated pauses was 20.6 ± 1.9 (SE) s, regardless of concentration (Figure 1I). Thus, IQGAP1 performs two actin-related activities: 1) it bundles actin filaments (Figure 1C) 34,38,[41][42][43] , and 2) it reduces overall actin filament assembly by transiently pausing elongation at the filament plus-end (Figure 1D-I).…”
Section: Iqgap1 Bundles and Temporarily Pauses Actin Filament Elongat...mentioning
confidence: 99%